Upaya Peningkatan Ketaatan Minum Obat Melalui Pemberian Leaflet pada Pasien Tuberkulosis Paru di Puskesmas Payung Sekaki Kota Pekanbaru - Erniza Pratiwi; Husnawati Husnawati; Farel Anugrah (Universitas Borneo Lestari, 2021)
The high level of mobility and population density, causing the spread and death caused by tuberculosis to increase. This study purpose was to evaluate the effectiveness of provision of leaflet to increase medication adherence for pulmonary tuberculosis patients at Puskesmas Payung Sekaki, Pekanbaru for the period February-April 2016 , The study design is a quasi-experimental with non-randomize control group pretest and posttest design. Sampling method uses by purposive sampling with appointed criteria, 20 respondents in the control group and 20 respondents in the intervention group. The results was using Wilcoxon and Mann-Whitney test, showed that there were significant differences of adherence for pulmonary tuberculosis patients before and after provision of leaflet. The efforts to increase medication adherence for pulmonary tuberculosis patients at Puskesmas Payung Sekaki, Pekanbaru through the provision of leaflets have shown a significant increase